2018
DOI: 10.1177/2516600x18774195
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dynamics of M&As in Indian IT Sector: An Analysis of the Trends, Patterns, and Directions

Abstract: This study attempts to explore the trend of M&As by IT companies having headquarters in India. The results reveal that trend across the time is not unidirectional. Global recession of 2008 significantly affected the number of deals. It has more severe impact on international deals than on domestic deals. The study also revealed that companies engaged in more international deals than the domestic deals with USA alone, accounting for 56 percent of international deals. For domestic M&As, it has been found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There are many studies that discussed trends of M&As in specific sectors and in an aggregate of all sectors across the globe (Reddy, 2015; Institute for Digital Research and Education [IMAA], 2017, etc.) and also in India (Saraswathy, 2010; Kar, Soni, & Singh, 2014; Kar & Soni, 2018, etc.). These studies show that there were no uniform trends of M&As in the twentieth century and in the first decade of the twenty-first century, but there were waves of M&As for different reasons and of different natures.…”
Section: Review Of Literaturementioning
confidence: 99%
“…There are many studies that discussed trends of M&As in specific sectors and in an aggregate of all sectors across the globe (Reddy, 2015; Institute for Digital Research and Education [IMAA], 2017, etc.) and also in India (Saraswathy, 2010; Kar, Soni, & Singh, 2014; Kar & Soni, 2018, etc.). These studies show that there were no uniform trends of M&As in the twentieth century and in the first decade of the twenty-first century, but there were waves of M&As for different reasons and of different natures.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Extant literature suggests the effects of various macroeconomic factors (Bhasin et al, 2020), international shocks (like the South-East Asian crisis in 1997, recession caused by the financial crisis in 2008, etc) (Kar et al, 2020;Soni et al, 2019) and firm-specific strategic reasons having impacted M&As in India (Kalra et al, 2013;Kar & Soni, 2018). Although, investigating the impacts of these factors on Indian M&As is beyond the scope of this study, yet our trend analysis reveals three significant peaks generated in the years 1999, 2000 and 2011. This may be attributed to those factors.…”
Section: Analysis Of Trends Of Mergers and Acquisitionsmentioning
confidence: 77%
“…As per the findings of Soni et al (2019), the economic recession of 2008-2009 was found to significantly reduce the M&A activities by Indian IT companies for the time period 2000-2015. The reduction in M&As activities was more in international deals than domestic deals after the subprime crisis, and the increase in the share of the market-seeking motive for domestic market reflects the fact that Indian IT companies looked inward for the market in the volatile period after the crisis (Kar & Soni, 2018). In a significant finding, Kar et al (2020) validated that the financial impact of domestic deals in long run per se is much better than cross-border deals from a study of Indian IT sector.…”
Section: Overview Of Literaturementioning
confidence: 87%